An efficient method for immature embryo rescue and plant regeneration from the Calli of Ziziphus jujuba 'Lengbaiyu'. Issue 1 (2nd January 2019) - Ren, Haiyan; Du, Xuemei; Li, Dengke; Zhao, Ailing; Wang, Yongkang; Xue, Xiaofang; Gong, Guihua; Du, Junjie
ABSTRACT: Hybrid breeding of Chinese jujube ( Ziziphus jujube ) is limited by embryo abortion. Improving the success of embryogenic progeny and immature embryo culture techniques could increase the breeding efficiency of new jujube varieties. We optimised the current immature embryo culture techniques by using immature embryos before the globular stage of Chinese jujube variety Lengbaiyu. The optimal growth media were as follows: for 30-day-old immature embryo growth, MS + IBA 0.8 mg·L −1 + ZT 0.5 mg·L −1 + GA3 7.0 mg·L −1 + NAA 0.2 mg·L −1 + LH 0.5 mg·L −1 + 5% sucrose, with 22.22% embryonic growth rate and 0.41% plantlet formation rate; and for young embryo differentiation, MS + TDZ (0.8 mg·L −1 ) + IAA (0.5 mg·L −1 ) + sucrose (3%), with 81.12% differentiation rate. Thus, regeneration via callus induction effectively improved the efficiency of embryo rescue from young immature embryos in Lengbaiyu, which might provide new approaches for breeding Chinese jujube.